TEACHING SPEAKING BY CONTEXT - Shabir, M. (ENGLISH JOURNAL, 2017)
This study investigates the teaching of speaking by context at a junior high school in Bogor, West Java. The data were collected through the teacher’s journal and questionnaires interpreted descriptively. The results indicate that teaching by context is useful in terms of creating a logical and well-structured teaching strategy, exposing students to a variety of learning activities, and connecting students to their real life and experiences. As a result, speaking performance and activity of the students could improve and become better. The results of the study are expected to contribute to the improvement of students’ speaking learning.